THE INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE IS MORE EFFECTIVE THAN CONTRACT RELAX STRETCHING TO ULTRASOUND MODALITY IN INCREASING NECK RANGE OF MOTION OF MYOFASCIAL SYNDROME IN UPPER TRAPEZIUS MUSCLE - Saraswati, Putu Ayu Sita; Antari, Ni Komang Juni; Negara, Anak Agung Gede Angga Puspa (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 2 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i02.p06, 2018)
ABSTRACT ``Myofascial pain syndrome in upper trapezius muscle is a muscle pain that implicated by one or some myofascial trigger points in upper trapezius muscle. Working with static position in long time stimulating the presence of myofascial trigger points that causing pain and movement limitation of the neck that stimulate neck disability. Physical therapy’s intervention for reducing pain in this case could be integrated neuromuscular inhibition technique or contract relax stretching combined with ultrasound modality. Purpose: to compare the both interventions in reducing neck disability of myofascial pain syndrome in upper trapezius muscle. Method: this was an experimental study with Randomized Pre and Post Test Group Design. Samples were divided into 2 treatment group that consist 12 samples for each group. The first group treated with integrated neuromuscular inhibition technique with ultrasound while the second group treated with contract relaxes stretching with ultrasound. The data was collected by measuring neck range of motion using goniometer at the time before and after treatment. Result: the 1st group showed that the Neck ROM increase 5.083±1.0840 (p<0.001) and the 2nd group showed that the Neck ROM increase 3.333±0.7780(p<0.001). It means there were significant effect of each treatment in both groups. The results of independent t-test showed p<0.001, so that there was significant difference of increased Neck ROM between these groups. The result of independent t-test showed p value 0.001, so there was significant difference between two groups at increasing neck ROM. Conclusion: combination integrated neuromuscular inhibition technique is more effective than contract relax stretching to ultrasound modality in increasing neck range of motion of myofascial syndrome in upper trapezius muscle. Keywords: myofascial, neck disability, trapezius, INIT, ultrasound, stretching